IMPELEMENTASI PENDIDIKAN SUFISME DALAM PENDIDIKAN ISLAM - Muis Sad Iman (MUADDIB Jurnal Kependidikan dan Keislaman, 2015)
Problems of modern society are including the disintegration of science, split personality, misuse of science and technology, silting faith, materialistic relationship patterns, justifying any means, stress and frustration. One way to overcome these problems is to develop a moral life and Sufism. Moral is self ornaments that bring benefit to those who do. He would like God and preferably human beings and other creatures. In it turned out to provide optimal guidance inwardly can integrate the human soul. And Mysticism or Sufism is a dimension of depth and confidentiality (esoteric) in Islam as law rooted in the Quran and al-Sunnah. It became the soul of the Islamic message as that of the body's heart hidden away from the outside view. However it remains as most source of life, which regulates the whole religious organism in Islam. Islamic education is a means in the formation of character and Sufism.